Caregiver-specific factors and orphanage-context factors contributing to maltreatment of children in institutional care: A multi-level analysis of 24 orphanages in Tanzania. (June 2022) - Mkinga, Getrude; Kirika, Anette; Nkuba, Mabula; Mgode, Simeon; Huth, Mira; Hecker, Tobias
Background : High rates of maltreatment and low caregiving quality in institutional care settings have been identified in various low-and middle-income countries. Many studies have focused on children living in institutions.Objective : This study investigates the prevalence of maltreatment, caregiver-specific, orphanage-context factors, and their relation to maltreatment of orphans from the caregivers' perspective.Participants and setting : In this cross-sectional study, 227 caregivers (67% female) with a mean age of 36.84 years ( SD age = 12.89) of 24 childcare centres in Dar es Salaam, Tanzania participated.Methods : The primary outcome was the maltreatment of children assessed through structured interviews of caregivers. Further information on individual (like work-related stress) and structural variables (working conditions) was gathered.Results : Caregivers' work under extreme and exhausting conditions, with very high caregiver-child ratios, low salaries, and almost no possibility to recover. Results also showed significant differences in the maltreatment level and structural and individual factors (e.g., payment and days of entitlement) between the orphanages. Caregiver's positive attitudes towards violence ( ƒ 2 attitudes = 0.19) and difficulties in the relationship with children ( ƒ 2 relationship = 0.05) significantly predicted maltreatment with moderate and small effects.Conclusions : The overall poor working conditions highlight the urgent need to reduce the caregivers' burden. In addition to this, addressing caregivers' positive attitudes and improving their interaction competencies with children may be a starting point to prevent maltreatment of children. Further investigation of structural factors contributing to maltreatment is essential to develop recommendations for the improvement and re-organization of childcare institutions.